PROGRAM BIMBINGAN KELOMPOK UNTUK MENINGKATKAN MOTIVASI BERPRESTASI PESERTA DIDIK : Studi Deskriptif terhadap Peserta Didik Kelas VII SMP Negeri 1 Maleber Kabupaten Kuningan Tahun Ajaran 2014/2015 - Aprina, Evin Mila (2015)
The research is motivated by the lack of enthusiasm of the students in studying the subjects, rarely attend school, rarely or not completing the task, not creative, even a decrease in quality of learning. The approach used in this research is quantitative approach with descriptive methods. The samples included 144 students of 7th grade SMP Negeri 1Maleber in the year 2014/2015. The research instrument used by non-test instrument which is the questionnaire form that regarding of the motivation achievement. The research results have shown that 25 people were in the high category, 98 people were in the medium category, and 21 people were in the low category. The conclusion of the research is a general description of the motivation achievement of student in 7th grade SMP Negeri 1 Maleber in the year 2014/2015, the result is in the medium kategory. Group counseling program is designed to increase the motivation of the students with low category.